2022
DOI: 10.3389/fendo.2022.1032822
|View full text |Cite
|
Sign up to set email alerts
|

Development of Type 1 Diabetes may occur through a Type 2 Diabetes mechanism

Abstract: BackgroundAt diagnosis of Type 1 Diabetes (T1D), 30% of the beta cells are dormant, i.e. alive, but inactive. This could reduce beta cell destruction, as cellular stress contributes to beta cell damage. However, the beta cells, that are still active, must produce more insulin and are therefore more vulnerable. The inactive beta cells represent a potential for restoring the insulin secretion.MethodsWe analyzed the expression of selected genes in islets from live, newly diagnosed T1D patients from the DiViD stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…At the time of T1D diagnosis, roughly one‐third of the beta cells have been destroyed, one‐third are infiltrated by immune cells, mainly lymphocytes, and one‐third are ‘sleeping’; these appear microscopically normal but produce no insulin and are not infiltrated 14 . We have found among newly diagnosed T1D patients, that the insulin receptors were 53.4% of the value for the control persons ( p = 0.00003) 11 . In contrast to the study of Kahn, 10 a recent study using living animals showed that lack of insulin receptors on the beta cells increased the insulin production and secretion 32 …”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…At the time of T1D diagnosis, roughly one‐third of the beta cells have been destroyed, one‐third are infiltrated by immune cells, mainly lymphocytes, and one‐third are ‘sleeping’; these appear microscopically normal but produce no insulin and are not infiltrated 14 . We have found among newly diagnosed T1D patients, that the insulin receptors were 53.4% of the value for the control persons ( p = 0.00003) 11 . In contrast to the study of Kahn, 10 a recent study using living animals showed that lack of insulin receptors on the beta cells increased the insulin production and secretion 32 …”
Section: Discussionmentioning
confidence: 76%
“…14 We have found among newly diagnosed T1D patients, that the insulin receptors were 53.4% of the value for the control persons (p = 0.00003). 11 In contrast to the study of Kahn, 10 a recent study using living animals showed that lack of insulin receptors on the beta cells increased the insulin production and secretion. 32 The beta-cell mass adapts to a lower activity level, for example, after a pregnancy or other situations, when the insulin need is reduced.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In humans, it has been discussed that certain cells can enter a hibernation-like state during an extreme rest. This might be seen in beta cells in newly diagnosed type 1 diabetes patients [11]. This suggests the potential importance of C24:2 sulfatide in certain tissues.…”
mentioning
confidence: 83%
“… 37 Thus, in these older children, type 1 diabetes is manifested symptomatically when significant numbers of β-cells are still present and the extent of insulitis is modest. In this situation, it is feasible that a defect in insulin secretion may contribute significantly to the reduction in circulating insulin concentrations 42 rather than this being caused solely by the annihilation of β-cells, as in younger children. This does not mean that β-cell demise is not a feature of older onset type 1 diabetes because these cells are undoubtedly lost (especially with increasing disease duration).…”
Section: Insulitis Profiles At Increasing Ages At Diagnosis Of Type 1...mentioning
confidence: 99%